EFEKTIVITAS MODEL COOPERATIVE TYPE MAKE A MATCH TERHADAP HASIL BELAJAR IPAS MATERI METAMORFOSIS SISWA KELAS III SEKOLAH DASAR - Nurwahid; Desty Dwi Rochmania (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning models that are enjoyable can foster students' interest in learning and enhance their creativity and learning outcomes. The cooperative type make a match model is a learning model that encourages students to actively search for matching cards containing questions and answers, making learning more interactive and enjoyable. This study aims to: 1) determine the learning outcomes of third-grade students at SDN Diwek I Jombang on metamorphosis material before implementing the cooperative type make a match model; 2) determine the learning outcomes after implementing the model; and 3) determine the effectiveness of the cooperative type make a match model on student learning outcomes. This research uses a quantitative approach with a pre-experimental design type, specifically the One Group Pretest-Posttest Design. The sample consisted of 31 third-grade students selected through saturated sampling technique. Data were collected through tests (pretest and posttest) and documentation. Data analysis used descriptive statistical analysis, normality test with Shapiro-Wilk, hypothesis testing with Paired Sample T-Test, and effectiveness test with N-Gain. The results showed: 1) the average pretest score before treatment was 68.13; 2) the average posttest score after treatment increased to 87.87; 3) the Paired Sample T-Test obtained a significance value of 0.000 <0.05, indicating a significant difference between pretest and posttest results. The N-Gain test showed an average score of 0.6112 in the medium category or 61.12% in the quite effective category. Thus, it can be concluded that the cooperative type make a match model is effective in improving the learning outcomes of third-grade students on metamorphosis material at SDN Diwek I Jombang.